ANALISIS PERUBAHAN PENDIRIAN BADAN USAHA BERBADAN HUKUM DALAM BISNIS PERSEORANGAN - Komeni, Wirdi Hisroh; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to analyze the changes in legal entities, particularly in sole proprietorships. Thee study employs a normative research approach utilizing the historical approach method, and the legal materials used include primary and secondary legal sources, such as legislation, legal journals, and expert opinions. The conclusion is drawn using deductive technique, elaborating from the general to the specific. The data obtained from this research pertain to the requirements for establishing a legal entity, which can be established by just one person without difficult conditions, such as shorter licensing processes and simpler requirements. The conclusion drawn is that the requirements for establishing a legal entity were previously less flexible as they did not reflect the current progress of the country, especially with the increasingly developed economic conditions. Therefore, it is appropriate for the government to be involved in the development of businesses in Indonesia, one of which is by facilitating administrative access.Keywords: Analysis, Changes, Legal Entity, Individual Business